Semi-automated braiding of complex, spatially branched FRP-structures. (15th November 2021) - Born, Larissa; Möhl, Claudia; Kannenberg, Fabian; Melnyk, Samantha; Jonas, Florian Alexander; Menges, Achim; Knippers, Jan; Gresser, Götz T.
Highlights: Semi-automated process enables braiding of large-scale spatially branched structures. Process workflow enables the generation of robot paths from the component CAD. 4-armed node proves the producibility of multi-branched structures. Abstract: In building industries, branched load-bearing structures are used for defined load transfer and load distribution. While fiber-reinforced plastics are established as concrete formwork for straight segments, node geometries are less available. This is caused by the complex manufacturing process of spatially branched, three-dimensional textile preforms. There are only few productive textile processes for the manufacture that are attractive to industry, the most common is braiding. However, setting up the process, including programming the mandrel path through the braiding machine and adjusting the fiber placement, is very time consuming, making the process unattractive despite high productivity. This paper presents a new digitalized process workflow for the fabrication which simplifies the process preparation and thus could establish the braiding process for rapid fabrication of spatially branched, three-dimensional geometries. The digitalized workflow is validated by manufacturing a 4-arm node structure consisting of a concrete-filled CFRP in a scale relevant to the building industry.